Aproximación general a la acción de extinción del dominio en Colombia. (2014)
Colombia has been a country immersed in a constant and persistent struggle to overcome a state of endemic violence generated by numerous actors, including drug trafficking and illicit enrichment. In order to address these problems, the Colombian constituent assembly consecrated the figure of expired ownership as a legal tool to combat illicit enrichment, as well as violence and poverty that this phenomenon entails. 26 years later, the action of expired ownership is one of the main instruments of the state to tackle illicit enrichment, but its social and legal development has been neither peaceful nor totally effective. This article discusses the general characteristics of this figure, exposing its criticisms and benefits, and its prospects for an effective implementation in Colombia.